2012
DOI: 10.1108/13639511211230156
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice and organizational commitment among South Korean police officers

Abstract: PurposeIn spite of the importance of officers' perception of organizational justice and its influence on organizational commitment, the policing literature lacks information about the relationship between the factors. Using job satisfaction as a mediator, this study aims to examine an indirect influence of organizational justice on police officers' commitment to their organization.Design/methodology/approachThis study employed a survey of 418 police officers in South Korea while on in‐service training. In expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
128
0
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 73 publications
9
128
0
19
Order By: Relevance
“…As hypothesised, distributive justice was also found to have a significant positive relationship with job satisfaction among the surveyed Indian officers. This finding is consistent with the limited research to date, where distributive justice was reported to be a significant positive predictor of satisfaction among South Korean and US officers (Crow et al, 2012;Farmer et al, 2003). The current finding makes sense.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As hypothesised, distributive justice was also found to have a significant positive relationship with job satisfaction among the surveyed Indian officers. This finding is consistent with the limited research to date, where distributive justice was reported to be a significant positive predictor of satisfaction among South Korean and US officers (Crow et al, 2012;Farmer et al, 2003). The current finding makes sense.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, as hypothesised, both procedural justice -promotions and procedural justice -performance evaluation were positively and significantly related to satisfaction. This is an important finding as it indicates that the relationship between organisational variables in the police remains similar across widely different cultures such as the US (Farmer et al, 2003), South Korea (Crow et al, 2012) and India. Among Indian officers, both measures of procedural justice significantly impacted job satisfaction even after controlling for age, gender, post location, tenure, educational level and position.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Over the years, researchers and practitioners have identified the number of factors associated with the turnover intentions. The main strand of the literatures primarily concentrated on limited antecedents to turnover intention and actual turnover [17] such as job dissatisfaction [10,18], lower commitment [10,19], general adjustment [18], stress or job tension [10], justice [20]. The findings from these studies suggest that higher organizational commitment, job satisfaction and fairness at work are negatively related with turnover intention.…”
Section: Introductionmentioning
confidence: 84%
“…The relationship between distributive justice, procedural justice and conflict management styles has triggered the attention of researchers in organizational behaviour such as Tatum and Eberlin (2008) and Crow et al (2012). They had conducted studies focusing on investigating the relationship of both justices and conflict management styles on organizational commitment each of the variables individually and separately.…”
Section: Introductionmentioning
confidence: 99%